2017
DOI: 10.1161/circresaha.116.310531
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Functional Characterization of Hypoxia-Induced Endoplasmic Reticulum Stress Regulating lncRNA (HypERlnc) in Pericytes

Abstract: Objective: Here, we investigate the effect of hypoxia-induced endoplasmic reticulum stress regulating long noncoding RNAs (HypERlnc, also known as ENSG00000262454) on pericyte function in vitro and its regulation in human heart failure and idiopathic pulmonary arterial hypertension. Methods and Results

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 28 publications
0
47
0
Order By: Relevance
“…LncRNA LINC01619 regulates miR-27a/FoxO1 and ER stress-mediated podocyte injury in DKD [ 93 ]. LncRNAs (HypERlnc) regulated by hypoxia-induced ER stress are identified in pericytes [ 94 ]. Therefore, ER-stress-regulated lncRNAs may have important functions in pathogenesis of kidney diseases.…”
Section: Ncrnas In the Early Stage Of Dkdmentioning
confidence: 99%
“…LncRNA LINC01619 regulates miR-27a/FoxO1 and ER stress-mediated podocyte injury in DKD [ 93 ]. LncRNAs (HypERlnc) regulated by hypoxia-induced ER stress are identified in pericytes [ 94 ]. Therefore, ER-stress-regulated lncRNAs may have important functions in pathogenesis of kidney diseases.…”
Section: Ncrnas In the Early Stage Of Dkdmentioning
confidence: 99%
“…The Dimmeler group has contributed much to our understanding of vascular homeostasis, and the mechanisms that go awry in the pathobiology of vascular disease. In the current investigation, they introduce an intriguing new determinant of pericyte behavior that becomes most apparent during hypoxia (1). …”
Section: Pericytes and Vascular Homeostasismentioning
confidence: 99%
“…Another study demonstrated that lncRNA ENSG 00000262454 correlated with pericyte markers in idiopathic pulmonary arterial hypertension. 10) In the case of CTEPH, Josipovic, et al 11) found that lncRNA NONHSAT 073641 was upregulated in the vascular samples of pa-miRNA-genes-lncRNA NETWORK IN CTEPH tients with CTEPH and were important for endothelial angiogenic function. Competing endogenous RNAs (ceRNA) was found to lead to the hypothesis that lncRNA could interact with the gene through microRNA (miRNA) by competing for endogenous inhibition.…”
mentioning
confidence: 99%